The Role of Management Accounting Systems, Energy Efficiency and Organizational Innovation in driving Competitive Advantage and Firm Performance - Sinaga, Obsatar; Roespinoedji, Djoko; Saudi, Mohd Haizam Mohd; Ghani, Erlane K. (International Journal of Energy Economics and Policy, 2019)
The current study analyzes the role of management accounting systems (MAS) in dealing the critical environmental problems and organizational image for fulfilling environmental and organizational objective by using the advanced and suitable empirical investigation of PLS-SEM. In particular, the current study investigates the role of MAS systems in driving energy efficiency and organizational reputation in Malaysian manufacturing firms. In addition, the contribution of the present study is extended to identify the contribution of organizational energy-efficient processing and reputation in enhancing the firm's competitiveness and performance. The results of partial least square confirm that energy efficiency and organizational reputation have positive and significantly influenced by the management accounting system. Also, energy efficiency and organization reputation have positively and significantly influenced the competitive advantage of the manufacturing firms. Finally, we found the evidence that competitive advantage has significantly and positively impact on firm performance in Malaysian manufacturing firms. Keywords: Management accounting system, energy efficiency, firm performance, Malaysia. JEL Classifications: M14, M41, M42 DOI: https://doi.org/10.32479/ijeep.7749